Phasor analysis of NADH FLIM identifies pharmacological disruptions to mitochondrial metabolic processes in the rodent cerebral cortex - Gómez, Carlos A; Sutin, Jason; Wu, Weicheng; Fu, Buyin; Uhlirova, Hana; Devor, Anna; Boas, David A; Sakadžić, Sava; Yaseen, Mohammad A (PLoS One, 2018)
Investigating cerebral metabolism in vivo at a microscopic level is essential for understanding brain function and its pathological alterations. The intricate signaling and metabolic dynamics between neurons, glia, and microvasculature requires much more detailed understanding to better comprehend the mechanisms governing brain function and its disease-related changes. We recently demonstrated that pharmacologically-induced alterations to different steps of cerebral metabolism can be distinguished utilizing 2-photon fluorescence lifetime imaging of endogenous reduced nicotinamide adenine dinucleotide (NADH) fluorescence in vivo. Here, we evaluate the ability of the phasor analysis method to identify these pharmacological metabolic alterations and compare the method's performance with more conventional nonlinear curve-fitting analysis. Visualization of phasor data, both at the fundamental laser repetition frequency and its second harmonic, enables resolution of pharmacologically-induced alterations to mitochondrial metabolic processes from baseline cerebral metabolism. Compared to our previous classification models based on nonlinear curve-fitting, phasor-based models required fewer parameters and yielded comparable or improved classification accuracy. Fluorescence lifetime imaging of NADH and phasor analysis shows utility for detecting metabolic alterations and will lead to a deeper understanding of cerebral energetics and its pathological changes.
Keywords: Mitochondria; Seizures; Humans; Rodentia; nelineární dynamika; Bicuculline; Models, Biological; NAD; záchvaty; Microscopy, Fluorescence, Multiphoton; lidé; mitochondrie; Biomarkers; zvířata; mozková kůra; Cerebral Cortex; potkani Sprague-Dawley; biologické markery; biologické modely; hlodavci; Intravital Microscopy; mikroskopie fluorescenční multifotonová; Rats, Sprague-Dawley; Animals; intravitální mikroskopie; Nonlinear Dynamics; Disease Models, Animal; bikukulin; modely nemocí na zvířatech